Peran Anggota Majelis Ta’lim Al-Akbar dalam Membangun Sikap Peduli pada Masyarakat Tanjung Barangan Kota Palembang - Hana Pertiwi; Tutik Pebrianti (Jurnal Aksi Dosen dan Mahasiswa, 2024)
Many people carry out ta'lim assembly activities in order to learn religious knowledge. One of the aims of the ta'lim assembly is to foster an attitude of concern for society. However, there are still many people who do not care about the surrounding environment, both those who actively participate in ta'lim assembly activities and those who are less active. Therefore, this service was carried out with the aim of fostering an attitude of social care for members of the Tanjung Barangan Ta'lim al-Akbar Council, Palembang City. The material in this service is carried out directly by providing direct understanding and also using qualitative descriptive methods to collect data obtained through observation, unstructured interviews and documentation. This service activity can be said to be successful in providing guidance to the management of the Ta'lim al-Akbar Council to have a caring attitude towards others, especially towards people in need. This service activity was successful because there were supporting factors such as: public awareness of good things; assistance and support from local authorities; and adequate facilities. However, there are also inhibiting factors, namely the lack of comprehensive information and miscommunication between congregations.